Electoral Integrity and Criminal Policy: Addressing Regional Election Offences in Democratic Governance - Bayu Arjunah; Syamsul Bachri; Aswanto; Khaleel Suliman Khaleel Alrahamnah; Mohammed Jasim Mohammed; Ruslan Renggong (PT. Islamic Research Publiser, 2026)
Electoral integrity constitutes a fundamental prerequisite for democratic governance, yet regional elections (pilkada) in Indonesia continue to face persistent challenges arising from electoral offences, including money politics, intimidation, abuse of authority, and administrative manipulation. This study aims to examine the construction of criminal provisions governing regional election offences under Law Number 10 of 2016 and to formulate a criminal policy framework capable of preventing violations throughout the electoral cycle. Employing normative legal research, this study adopts a statutory, conceptual, and case-based approach. Primary legal materials consist of the 1945 Constitution of the Republic of Indonesia, regional election legislation, electoral regulations, and implementing rules issued by the General Election Commission (KPU) and the Election Supervisory Agency (Bawaslu). Secondary materials include legal doctrines, scholarly books, and peer-reviewed journal articles. The collected materials are analyzed through qualitative legal reasoning to identify normative inconsistencies and evaluate the effectiveness of existing enforcement mechanisms. The findings reveal that regional election offenses are fragmented across multiple regulatory provisions, predominantly characterized as formal offenses, and enforced within restrictive procedural timelines that depend heavily on inter-institutional coordination within the Integrated Law Enforcement Center (Gakkumdu). Consequently, criminal sanctions function primarily as a reactive instrument rather than an effective mechanism for electoral prevention and integrity protection. This study proposes a reorientation of criminal policy through the strengthening of core electoral offences, particularly those related to money politics, intimidation, administrative falsification, and abuse of public office; the integration of administrative and criminal sanctions; the simplification of evidentiary requirements; and the institutionalization of preventive measures based on campaign finance transparency, participatory oversight, and electoral risk management. These findings contribute to the development of electoral criminal law scholarship by advancing a preventive-oriented criminal policy model that reinforces electoral integrity and democratic accountability in regional governance.